Exhibition Dan Convention Di Tembilahan Dengan Pendekatan Arsitektur Ekspresionis - Yuharlis, Muhammad Gusman; Hidayat, Wahyu; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The promotion that is being done by the government of Indragiri Hilir District in various sectors is a way to improve the regional economy. Various exhibitions and meetings held annually become routine agenda and always be an attraction for local and foreign people. Toaccommodate the various exhibitions and meetings, it is necessary exhibition buildings and conventions with functional and large capacity room facilities. Design methods in designing apply an expressionist architectural approach in which the physical and characteristicbuildings and regions tend to blend the function and aesthetic aspects of both shape, space and structure. In addition to the shape taken from the concept characteristic "transaction"characterizes the building itself connected to the design principles.Keyword : Exhibition, Convention, Arsitektur Ekspresionis